(untitled) (Terr@ Plural, 2022)
The spatial concentration of productive activities and the consequent formation of regions characterized by a given productive specialization are topics of permanent interest for economic geography. In the current historical period, marked by globalization, the processes of concentration and productive specialization are characterized by relations between local and regional conditions and global dynamics. Considering the relevance of Brazil’s participation in the global production of tilapia (Oreochromis niloticus) and, in the Brazilian context, the importance of this activity in the state of Paraná, this article analyzes the particularities of the spatial circuits of production (production-distribution-exchange-consumption) and cooperation circles that define two main regional contexts in the territory of Paraná, the west and the north, in which this productive activity is concentrated. The results obtained demonstrate that the spatial conditions enable different manifestations of tilapia culture in the regional contexts analyzed, resulting in different technical modalities, and different material and immaterial flows, even though both produce the same commodity, tilapia.